Entrepreneurial Endeavors: Examining The Role of Catering Businesses In Pasuruan's Economic Empowerment - Setyo Tri Wahyudi; Nurul NBadriyah; Rilla Anggraeni; Mohamad Khusaini; Kartika Sari; Rihana Sofie Nabella; Radeetha Radeetha (International Journal Of Community Service, 2024)
This study explores the challenges faced by Muslim women in establishing catering businesses, primarily due to inadequate marketing strategies. To overcome these obstacles, the research proposes catering business assistance with a focus on utilizing the internet as a platform for product promotion. Incorporating the Marketing 4.0 concept, the study emphasizes the complementary nature of digital-based and traditional marketing to meet consumer demands. The evolution from the AIDA concept to the 4A and 5A models is examined, highlighting attention, attitude, action, and advocacy as essential elements in consumer engagement. The effectiveness of e-commerce is underscored by offering benefits for MSMEs, such as accessing buyers from different regions, cost efficiency, and improved communication. Online media, including platforms like WhatsApp, social media, and email marketing, is discussed for its positive impact on information processing, purchasing decisions, and expanding market networks. The study also emphasizes the need to combine online and offline strategies to enhance digital technology adoption, maintain a personal touch for consumer relationships, and widen business reach. This research emphasizes the importance of digital technology for MSMEs to thrive in the catering industry.